Development of a gestational age–specific case definition for neonatal necrotizing enterocolitis - Battersby,CWS; Longford,N; Costeloe,K; Modi,N (JAMA Pediatrics, 2017)
Importance Necrotizing enterocolitis (NEC) is a major cause of neonatal morbidity and mortality. Preventive and therapeutic research, surveillance, and quality improvement initiatives are hindered by variations in case definitions.Objective To develop a gestational age (GA)–specific case definition for NEC.Design, Setting, and Participants We conducted a prospective 34-month population study using clinician-recorded findings from the UK National Neonatal Research Database between December 2011 and September 2014 across all 163 neonatal units in England. We split study data into model development and validation data sets and categorized GA into groups (group 1, less than 26 weeks’ GA; group 2, 26 to less than 30 weeks’ GA; group 3, 30 to less than 37 weeks’ GA; group 4, 37 or more weeks’ GA). We entered GA, birth weight z score, and clinical and abdominal radiography findings as candidate variables in a logistic regression model, performed model fitting 1000 times, averaged the predictions, and used estimates from the fitted model to develop an ordinal NEC score and cut points to develop a dichotomous case definition based on the highest area under the receiver operating characteristic curves [AUCs] and positive predictive values [PPVs].Exposures Abdominal radiography performed to investigate clinical concerns.Main Outcomes and Measures Ordinal NEC likelihood score, dichotomous case definition, and GA-specific probability plots.Results Of the 3866 infants, the mean (SD) birth weight was 2049.1 (1941.7) g and mean (SD) GA was 32 (5) weeks; 2032 of 3663 (55.5%) were male. The total included 2978 infants (77.0%) without NEC and 888 (23.0%) with NEC. Infants with NEC in group 1 were less likely to present with pneumatosis (31.1% vs 47.2%; P = .01), blood in stool (11.8% vs 29.6%; P < .001), or mucus in stool (2.1% vs 5.6%; P = .048) but more likely to present with gasless abdominal radiograp